Analysis of Potential Review as a Catalyst for Character Building for Police Members - Fahri Kamuli*; Rosatyani Puspita Adiati; Yowan Tamu; Sukarman Kamuli (Universitas Syiah Kuala, 2024)
This study aims to evaluate the suitability between the potential and competence of Polri members in order to project them to occupy certain positions, in accordance with Perkap Number 3 of 2019 concerning Talent Management for the National Police of the Republic of Indonesia, which states that every member has the same right to develop their competence. The research method used was descriptive through case studies, with a sample of one member of the National Police at the Gorontalo Regional Police. Data was collected through individual assessments using test and non-test methods, and analyzed descriptively. The research results show that individual assessments provide a comprehensive picture of the competencies possessed by members of the Indonesian National Police and identify areas that need to be developed. The conclusion of this research is that competency mapping using the Human Asset Value Matrix is effective in identifying the suitability of the potential and competence of Polri members. The suggestions and recommendations put forward are for police institutions to implement regular individual assessments to maximize the development of member competencies, as well as use the results of these assessments to improve human resource management processes in the organization.